Evaluation of silkworm pupa meal on growth, body indices, digestive enzymes and histopathology of Cirrhinus mrigala fingerlings - Fatima Yasin; Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Syed Zakir Hussain Shah; Zawar Hussain; Waseem Abbas (Journal of Fisheries, 2025)
The world's growing population needs food, and aquaculture; a fast growing food producing sector, provides it. Fish meal (FM) is a major feed source in the aquaculture industry, but its low profitability and scarcity have prompted a quest for high-protein substitutes. Because silkworm pupa meal is inexpensive and has a high protein (50–60%) concentration, it was utilized as a substitute for fish feed. The goal of the current study was to determine the ideal proportion of silkworm pupa meal (SPM) to substitute for FM while creating an affordable feed for Cirrhinus mrigala fingerlings (average total length: 6 cm; average weight: 8 g). The fingerlings were fed six test diets (0, 20, 40, 60, 80, and 100%) at a rate of 4% of their live wet body weight twice a day. Diets contained chromium oxide as an inert marker. The feeding trial lasted for ninety days. The fingerlings' weight was measured every 14 days to calculate growth metrics (weight gain percentage, FCR, and SGR). Following the conclusion of the trial, intestinal histology, digestive enzyme function, and body indices were examined. Highest growth rate (WG%: 333%, SGR: 1.64, FCR: 1.26, CF: 1.50) and best body indices (hepatosomatic index: 1.95, viscerosomatic index: 6.43) values were observed at 40% replacement of FM. Intestinal histological analysis and digestive enzyme activity demonstrated that SPM can be readily substituted up to 40% without affecting the general performance of C. mrigala fingerlings and aid in creating an economical and environmentally friendly diet.